2011
DOI: 10.1530/eje-11-0599
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of the metabolic syndrome in 2479 hypopituitary patients with adult-onset GH deficiency before GH replacement: a KIMS analysis

Abstract: Objective: An increased risk of cardiovascular morbidity and mortality in adult GH deficiency (GHD) may be related to hypopituitarism but also to the presence of the metabolic syndrome (MetS). Our objective was to investigate the characteristics and prevalence of MetS as well as its comorbidities in adult GHD. Design: In KIMS (Pfizer International Metabolic Database) 2479 patients with severe adult-onset GHD, naïve to GH replacement, with complete information on all MetS components were found. MetS was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 39 publications
10
50
0
5
Order By: Relevance
“…This was apparent in both genders, but crude analysis and regression analysis showed that it occurred at a slower pace compared with the increase in the reference population. This latter observation could be due to the fact that in the general reference population diabetes prevalence is relatively low in young adults, resulting in an elevated SPR, and to the increased prevalence of risk factors for diabetes in GHD patients, as reported previously (23). Other factors related to a younger age, such as a profound clinical impact of obesity inducing a more rapid insulin resistance, have been proposed (24).…”
Section: Discussionmentioning
confidence: 74%
“…This was apparent in both genders, but crude analysis and regression analysis showed that it occurred at a slower pace compared with the increase in the reference population. This latter observation could be due to the fact that in the general reference population diabetes prevalence is relatively low in young adults, resulting in an elevated SPR, and to the increased prevalence of risk factors for diabetes in GHD patients, as reported previously (23). Other factors related to a younger age, such as a profound clinical impact of obesity inducing a more rapid insulin resistance, have been proposed (24).…”
Section: Discussionmentioning
confidence: 74%
“…Hypopituitarism, and in particular GHD are associated with several metabolic alterations and cardiovascular risk [6][7][8]17,[23][24][25][26].This brief report showed that also in hypopituitarism due to TBI metabolic impairment is frequent, in particular altered glucose levels, insulin resistance and dyslipidemia, independently by BMI.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, altered body composition, insulin resistance, hypertension, unfavorable lipid profile, endothelial dysfunction and atherosclerosis has been reported in several studies on treatment of naïve GH deficient patients along time [6][7][8][11][12][13][14][15][16]. Accordingly, also metabolic syndrome prevalence is present in GH deficient patients and may therefore contribute to the increased risk of cardiovascular morbidity and mortality found in these patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…Adults with GHD also present with metabolic abnormalities that resemble those of the metabolic syndrome [Johansson and Bengtsson, 1999], which itself is a strong predictor of T2DM risk. Data from other surveillance studies of patients treated with recombinant hGH indicate that the prevalence of the metabolic syndrome is higher in GHD patients (40-50%) than in the general population (20-30%) [Attanasio et al 2010;Verhelst et al 2011]. In one study, while prevalence was unaffected by GH replacement therapy, baseline metabolic syndrome status or obesity were strong predictors of the metabolic syndrome after 3 years of GH treatment [Attanasio et al 2010].…”
Section: Data Collection and Analysismentioning
confidence: 90%